2015
DOI: 10.1097/ico.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Central and Peripheral Corneal Stromal Demarcation Line Depth in Conventional Versus Accelerated Collagen Cross-Linking

Abstract: The stromal demarcation line depth was shallower after accelerated CXL compared to that of conventional CXL at the corneal center and its periphery. The volume of cross-linked stroma appears to be larger after conventional CXL compared to its accelerated counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
1
15
0
4
Order By: Relevance
“…Despite several studies on this subject, the effective depth for arresting disease progression remains unknown, and there is still debate over the efficiency of cross-linking in the anterior part of the cornea. The depth of the demarcation line in the center of the cornea has been reported to be between 300 and 400 μm with the standard protocol, 6 , 7 , 8 about 323 μm with the 14-min protocol, 12 from 203 μm up to 288 μm with the 10-min approach, 9 , 10 , 16 about 247 μm with the 9-min protocol, 11 and 223 μm with the 5-min protocol. 13 These results indicate reduced line depth with shorter exposure times, although there may be considerable variations in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies on this subject, the effective depth for arresting disease progression remains unknown, and there is still debate over the efficiency of cross-linking in the anterior part of the cornea. The depth of the demarcation line in the center of the cornea has been reported to be between 300 and 400 μm with the standard protocol, 6 , 7 , 8 about 323 μm with the 14-min protocol, 12 from 203 μm up to 288 μm with the 10-min approach, 9 , 10 , 16 about 247 μm with the 9-min protocol, 11 and 223 μm with the 5-min protocol. 13 These results indicate reduced line depth with shorter exposure times, although there may be considerable variations in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…указывают на выявление демаркационной линии с помощью ОКТ через 1 месяц после процедуры кросслинкинга только в 75% случаев, причем демаркационная линия через 3 месяца не опре-делялась ни в одном случае [10]. Аналогичные данные были получены и в работе Alex и соавт., которые конста-тировали наличие демаркационной линии в 79% случаев через 1 месяц после кросслинкинга роговицы [13].…”
Section: Discussionunclassified
“…Имеются единичные публикации о различиях в глубине залегания ДЛ в центральном и перифериче-ских секторах роговицы (в 3 мм назальнее и темпораль-нее центра) [12]. При применении стандартного прото-кола кросслинкинга, в отличие от акселерированного, выявлено более глубокое залегание демаркационной линии, что может объяснить различную клиническую эффективность в результате применения этих протоко-лов [13,14]. Цель: оценка топографической локализации демаркационной линии в различных секторах роговицы после стандартного кросслинкинга роговицы.…”
unclassified
“…Some investigators have observed a shallower postoperative demarcation line, indicating reduced riboflavin penetration and CXL treatment depth [ 106 ]. However, Kymionis et al using modified accelerated protocols (18 mW/cm 2 for 7 min and 9 mW/cm 2 for 14 min) found no difference in the depth of the demarcation line in comparison to standard CXL [ 107 ].…”
Section: Current Treatment Options and Managementmentioning
confidence: 99%